Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1979031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating swabbing

Abstract: Elderly users suffering from hand tremor have difficulties interacting with touchscreens because of finger oscillation. It has been previously observed that sliding one's finger across the screen may help reduce this oscillation. In this work, we empirically confirm this advantage by (1) measuring finger oscillation during different actions and (2) comparing error rate and user satisfaction between traditional tapping and swabbing in which the user slides his finger towards a target on a screen edge to select … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…For example, Kane et al proposed more general guidelines for developing mobile services for people with visual and motor disabilities, such as support for highly flexible interface customization to arbitrary settings, and dynamic adaptation of user interface to increase accessibility in different outdoor environments [56]. More specific design approaches have been created to facilitate interactions for people with specific needs, such as sliding fingers on the screen instead of tapping for people suffering from tremors [57] or using pens and edges on the screen for people with motor issues [58]. Participants in our study also gave us some suggestions on how they usually address these problems when using their private mobile devices and proposed how the Connect Mobile app could be adapted to be more suitable to their needs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kane et al proposed more general guidelines for developing mobile services for people with visual and motor disabilities, such as support for highly flexible interface customization to arbitrary settings, and dynamic adaptation of user interface to increase accessibility in different outdoor environments [56]. More specific design approaches have been created to facilitate interactions for people with specific needs, such as sliding fingers on the screen instead of tapping for people suffering from tremors [57] or using pens and edges on the screen for people with motor issues [58]. Participants in our study also gave us some suggestions on how they usually address these problems when using their private mobile devices and proposed how the Connect Mobile app could be adapted to be more suitable to their needs.…”
Section: Discussionmentioning
confidence: 99%
“…When touchscreen input was compared with mouse input, Findlater et al [35] found that though touchscreen input was faster for people with motor impairments, it also led to a three-fold increase in pointing (tapping) errors on the touchscreen compared to the mouse. Some approaches to address these problems have used the edge of the screen to stabilize gestures [38,140], or a swiping ("swabbing") interaction rather than tapping, which allows the user to stabilize their finger on the screen itself [135]. For common touchscreen gestures like tapping, crossing and directional gesturing, Guerreiro et al [45] found that targets located at the bottom of the screen and next to the preferred hand were the easiest to select.…”
Section: Accessible Mobile Computingmentioning
confidence: 99%
“…On the other hand, many studies have focused on making these mobile computing devices accessible. Some examples include utilizing the physical edges of the device [38,140] for better gesture stability, or touching and sliding the finger (called swabbing) [135] for target selection or analyzing touchscreen gestures to better understand the input preferences for people with motor impairments [35,45]. Particularly for wheelchair users and more closely related to my dissertation, Carrington et al [21] explored alternative input/output spaces on and around the wheelchair for accessible mobile computing and later, built a pressure-sensitive input technique on the armrest of the wheelchair to help people with motor impairments interact with mobile computing devices [22].…”
Section: Chapter 1 : Introduction Motivationmentioning
confidence: 99%
“…In another invention, Montague et al introduced the Shared User Modeling Framework [25], an adaptive framework that aimed to improve touch accessibility across devices and applications. Wacharamanotham et al evaluated Swabbing [38], a technique for elderly adults to acquire targets by dragging their finger across a target rather than discretely tapping it. Unlike these techniques, which focused primarily on single finger touch input, Smart Touch improves touch accuracy while allowing users to interact with the screen in whichever way is most comfortable and natural for them.…”
Section: Understanding Touch Screen Accessibility For People With Motmentioning
confidence: 99%